MAIT cells in the liver environment - Mehta, H (2020)
MAIT cells are an important innate T cell population capable of recognising riboflavin-derived ligands presented by the evolutionary conserved MR1 molecule. The ability to activate MAIT cells either through their TCR or cytokines alone enables them to respond to both bacterial and viral infections. The liver is a common site of bacterial and viral infection, due partly to its anatomical setting and partly its tolerogenic environment. MAIT cell enrichment and function in the liver and their impairment in liver and non-liver diseases is not fully defined/understood. In this project I looked closely at the individual, liver resident, cell-specific influence on MAIT cells and their possible role in liver protection or pathogenesis. Using liver cell lines and primary MAIT cell co-cultures and flow cytometry I investigated the ability of liver resident cells to influence primary MAIT cells derived from healthy donors. I have identified that MAIT cells could be activated by LECs using both MR1 and cytokine pathway in response to bacterial stimuli which was not seen with hepatocytes or hepatic stellate cells. MAIT cells were suppressed indirectly in a contact-independent manner, by a small, soluble, COX-dependent, hepatocyte specific mediator/s. Strong suppression of MAIT IFN- by prostaglandins and a partial recovery with COX inhibitor treatment of hepatocytes strongly indicate the role of prostaglandins as well as other factors in controlling MAIT cell activation and function. Prostaglandins can be produced by several liver cell types, are primary involved in liver homeostasis and regeneration but can also impact MAIT cell function by potently suppressing their pro-inflammatory and cytotoxic capacity. The role of MAIT cells in liver disease was analysed by high dimensional, multiparametric spectral flow cytometry. MAIT cell numbers declined significantly in cirrhosis and LT, displayed an exhausted phenotype and were highly dysfunctional. Unsupervised analysis of the same cohort reveals exhaustion and loss of several MAIT cell-related populations which had reduced cytotoxic and inflammatory potential. Overall our data identifies the potential for MAIT cell activation by liver resident cells which can be altered by paracrine signals from neighbouring cells. Furthermore, the loss and functional defects in MAIT cells results in reduced liver protection.